Implementasi Intrusion Prevention System (IPS) Untuk Menganalisis Triad CIA Terhadap Serangan Keamanan Jaringan Pada Web Server - Amilia Anggraeni; Jafaruddin Gusti Amri Ginting; Syariful Ikhwan (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
Computer networks are built to achieve the main goal of communicating with each other . During the transmission process, it is expected that information can be conveyed quickly, efficiently and safely. Network security serves to avoid damage or even data loss caused by attacker activities during the communication process. Security aspects that need to be maintained in data information are Confidentiality, Integrity and Availability. Intrusion Prevention System is a solution that can maintain network security from various attacks. The Intrusion Prevention System will act as a protector on the network by detecting and preventing suspicious traffic on nodes in a network. The Intrusion Prevention System in its implementation has several tools which are used in this study, namely Snort and IPTables. Testing is done by performing attacks on the Web Server. The attacks carried out are Port Scanning, DDoS attacks and Brute Force. The results of this study are based on the CIA Triad with the three attacks having different characteristics in terms of cause and effect. On the defense side, Port Scanning and Brute Force can be easily prevented by IPS, but in DDoS attacks there are differences in results between drop and reject rule. In a DDoS attack with an action drop rule, it can recover the web server in 160 seconds while the action reject rule can be restored at 145 seconds which normally can be recovered in a DDoS attack in 165 seconds. The IPS server can also reduce resources when there is a DDoS attack by 9.2% .